Menentukan Desain Struktur Atas Gedung Fajar Biru Trenggalek Berdasarkan SNI (Standart Nasional Indonesia) - Alfin Dino Saputra; Edy Gardjito; Sigit Winarto; Muhammad Heri Nastotok; Faiz Muhammad Azhari (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
A multi-storey reinforced concrete building is very prone to collapse. Therefore, proper structural planning is needed in order to qualify the strength and security of the structure. Fajar Biru Building is a building that will be built in Karangsuko village of Trenggalek Regency, East Java. The building functioned as a cost with a building area of 340 m2, and has a total of 4 floors. The method used is the SRPMM (Medium Moment Musician Frame System) method which refers to SNI 1726:2012, and SNI 2847:2013. Planning includes the calculation of beams, floor plates, and columns. From the results of the calculations that have been done. on the floor plate structure with a plate thickness of 120 mm, Ø12 tree bones are used with a distance of 100 mm for pedestals and 150 mm for field areas. On the looping of B1 beams with dimensions of 300x350 mm used 6-D16 tree bones for focus and 4-D16 for field areas with Ø10-70 mm for focus and Ø10-140 mm for field areas. For the repeating of Column K1 with dimensions of 300x600 mm used 10-D16 principal bones with a Ø10-70 mm dimension. So that from these results can be used as a reference in the implementation of the construction of the blue dawn building.